1999
DOI: 10.1094/cchem.1999.76.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amylopectin Branch Chain Length and Amylose Content on the Gelatinization and Pasting Properties of Starch

Abstract: Cereal Chem. 76(5):629-637Structures and properties of starches isolated from different botanical sources were investigated. Apparent and absolute amylose contents of starches were determined by measuring the iodine affinity of defatted whole starch and of fractionated and purified amylopectin. Branch chainlength distributions of amylopectins were analyzed quantitatively using a high-performance anion-exchange chromatography system equipped with a postcolumn enzyme reactor and a pulsed amperometric detector. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

125
912
15
33

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,402 publications
(1,085 citation statements)
references
References 26 publications
125
912
15
33
Order By: Relevance
“…A higher amylose content and longer chain-length of amylopectin are known to affect pasting properties. 27 The results in this study confirmed the altered molecular structure seen by gel permeation chromatography.…”
Section: Molecular Characterization Of Potato Starchsupporting
confidence: 81%
“…A higher amylose content and longer chain-length of amylopectin are known to affect pasting properties. 27 The results in this study confirmed the altered molecular structure seen by gel permeation chromatography.…”
Section: Molecular Characterization Of Potato Starchsupporting
confidence: 81%
“…The low gelatinization of potato starch is considered to be partly due to the higher levels of phosphate monoester derivatives compared to starches found in grains, and the abundance of the B-type crystalline structures (Jane et al, 1999). The negative charges of the phosphates adjacent to the amylopectin chains repel each other, weakening the hydrogen bonds in the crystalline structure.…”
Section: Blanchingmentioning
confidence: 99%
“…The negative charges of the phosphates adjacent to the amylopectin chains repel each other, weakening the hydrogen bonds in the crystalline structure. These weakening bonds then allow water to readily destabilize the granular structure, reducing the gelatinization temperature (Jane et al, 1999). The B-type structure is characterized by a large proportion of long amylopectin branches (Gilbert, Besnard, Reeve, Lambides, & Hasjim, 2013) and fewer short branches (Hizukuri, Takeda, & Yasuda, 1981).…”
Section: Blanchingmentioning
confidence: 99%
“…In particular, it is one of the most important rheological indicators of the cooking quality and processing characteristics of rice. The amylose content and branch chain length distribution have also been found to have a substantial impact on the swelling and pasting properties of rice starches (Tsai et al, 1997;Jane et al, 1999). To examine the gelatinization characteristics of the four rice cultivars under analysis in this study, the swelling and thermal properties of their starches were measured using method of Li and Yeh (2001) and a differential scanning calorimeter, respectively.…”
Section: The Gelatinization and Swelling Of Rice Starchesmentioning
confidence: 99%
“…Moreover, gelatinization in this cultivar was complete at about 100℃ and occurred over a range that is 10℃ higher than that of the other starches. Jane et al (1999) have reported that the chain length and distribution of amylopectin branches determines the gelatinization temperature of starch, in addition to the enthalpy changes, and pasting properties, and that this temperature increases with the interactions between longer chains within the amylopectin cluster. The gelatinization enthalpy (∆H), which is the energy required to melt rice starches, showed energy content differences ranging between 7.4 and 8.8 J/g, and was found to be highest in Ilpum.…”
Section: The Gelatinization and Swelling Of Rice Starchesmentioning
confidence: 99%